2006
DOI: 10.1088/0957-4484/17/5/028
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nanopillars by nanosphere lithography

Abstract: A low cost nanosphere lithography method for patterning and generation of semiconductor nanostructures provides a potential alternative to the conventional top-down fabrication techniques. Forests of silicon pillars of sub-500 nm diameter and with an aspect ratio up to 10 were fabricated using a combination of the nanosphere lithography and deep reactive ion etching techniques. The nanosphere etch mask coated silicon substrates were etched using oxygen plasma and a time-multiplexed ‘Bosch’ process to produce n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
211
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(214 citation statements)
references
References 18 publications
2
211
0
1
Order By: Relevance
“…Forests of silicon pillars with diameters of sub-500 nm and an aspect ratio of up to 10 were have been fabricated by firstly conduct O 2 RIE to turn close-packed PS particle monolayers to non-close packed on and subsequently conduct a "Bosch" process to etch the supporting silicon wafers [53]. Sow et al have demonstrated the characteristic features of a RIE silicon substrate using a PS colloidal crystal mask and produced a double dome structure by simultaneous etching of the mask and the regions beneath the particles [54].…”
Section: Controllable Etchingmentioning
confidence: 99%
“…Forests of silicon pillars with diameters of sub-500 nm and an aspect ratio of up to 10 were have been fabricated by firstly conduct O 2 RIE to turn close-packed PS particle monolayers to non-close packed on and subsequently conduct a "Bosch" process to etch the supporting silicon wafers [53]. Sow et al have demonstrated the characteristic features of a RIE silicon substrate using a PS colloidal crystal mask and produced a double dome structure by simultaneous etching of the mask and the regions beneath the particles [54].…”
Section: Controllable Etchingmentioning
confidence: 99%
“…Island lithography (ISL) and nanosphere lithography (NSL) are well established techniques that can be combined with a vertical etching process to form disordered or ordered arrays of nanopillars (see, e.g., [5][6][7]). Further metallization and ion etching steps can be performed to enable the fabrication of plasmonic antennas and a possible parallel fabrication scheme is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[110,111] Nanosphere lithography (NSL) [34] exploits the self-assembly of colloids in the costeffective generation of mono-and bilayer colloidal crystal masks for various postprocessing steps, including metal deposition, [34] SAM formation [112] and reactive ion etching. [113] After removal of the colloids by lift-off, large-area arrays of functional nanostructures are left on the surface of the substrate. For NSL, most contributions exploit the resulting metal nanostructure arrays after metal deposition as templates in the transformation to metal nanoparticles by thermal annealing, [114] as catalysts in the generation of silicon nanopillars by molecular beam epitaxy, [115] carbon nanofibers (CNFs) [116] and ZnO nanopillars [117] by chemical vapor deposition (CVD), as etch masks in the fabrication of nanoimprint molds [118] and 2D photonic crystal patterns [119] by reactive ion etching, and as wet-etch masks in the gener nan ien …”
Section: Nanosphere Lithographymentioning
confidence: 99%
“…Control over the lateral dimensions and the periodicity of the metal structure arrays is feasible by O 2 plasma, [113] thermal annealing, [121] or ion polishing [122] and by adjusting the diameter of the colloidal particles, respectively. According to computer simulations, [121] it is within the capability of NSL to generate several different feature shapes by adjusting the relative position of the evaporation source during deposition.…”
Section: Nanosphere Lithographymentioning
confidence: 99%